Using Universal Line Model (ULM) for Representing Electromagnetic Transients in Three-Phase Transmission Lines - Araujo, A. R. J. de [UNESP]; Silva, R. C. da; Kurokawa, S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2014)
The second-order differential equations that describe the polyphase transmission line are difficult to solve due to the mutual coupling among them and the fact that the parameters are distributed along their length. A method for the analysis of polyphase systems is the technique that decouples their phases. Thus, a system that has n phases coupled can be represented by n decoupled single-phase systems which are mathematically identical to the original system. Once obtained the n-phase circuit, it's possible to calculate the voltages and currents at any point on the line using computational methods. The Universal Line Model (ULM) transforms the differential equations in the time domain to algebraic equations in the frequency domain, solve them and obtain the solution in the frequency domain using the inverse Laplace transform. This work will analyze the method of modal decomposition in a three-phase transmission line for the evaluation of voltages and currents of the line during the energizing process.
Keywords: Electromagnetic Transients; transmission lines; modal decomposition; distributed parameters